Analysis Of The Application Of Sales And Cash Receipt Accounting Information Systems To Internal Control In Cv. Wahana Ban - Cinta Nikita Aulia; Fitri Yani Panggabean; M. Irsan Nasution (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the implementation of sales and cash receipt accounting information systems and their impact on internal control effectiveness at CV. Wahana Ban. This research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation related to sales procedures, cash receipts, and internal control practices within the company. The results indicate that the sales and cash receipt accounting information system at CV. Wahana Ban has been computerized and supports real-time transaction recording through the use of the Ethaner system. However, the implementation of internal control has not been fully optimal. Several weaknesses were identified, including the lack of clear segregation of duties between cash receipt and recording functions, the absence of formal documentation for inventory release from the warehouse, and the absence of regular internal audits. Based on the COSO internal control components, the control environment, control activities, and information and communication components have been implemented adequately, while risk assessment and monitoring require further improvement. This study is expected to provide useful insights for companies in enhancing accounting information systems to strengthen internal control effectiveness.